2000
DOI: 10.1161/01.hyp.35.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transforming Growth Factor-β1 in Cardiovascular Inflammatory Changes Induced by Chronic Inhibition of Nitric Oxide Synthesis

Abstract: Abstract-We previously reported that chronic inhibition of nitric oxide (NO) synthesis with N -nitro-L-arginine methyl ester (L-NAME) induces inflammatory changes (monocyte infiltration, myofibroblast formation, and monocyte chemoattractant protein-1 [MCP-1] and transforming growth factor-␤1 [TGF-␤1] expression) in the rat heart and vessel. There is debate regarding whether TGF-␤1 exhibits proinflammatory or anti-inflammatory activities. We used the rat model to investigate the role of TGF-␤ in the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 38 publications
2
43
0
2
Order By: Relevance
“…9 -11 It has been shown that an anti-pan-TGF-␤ monoclonal NAb effectively prevents the expression of extracellular matrix proteins and subsequent myocardial fibrosis in rats with long-term blockade of nitric oxide synthesis. 12 Therefore, using the NAb, we investigated the roles of TGF-␤ in myocardial remodeling in PO rats with a suprarenal abdominal aortic constriction (AC). Also, we examined whether prevention of myocardial remodeling by blocking TGF-␤ function would improve cardiac dysfunction in PO rats.…”
Section: Iastolic Dysfunction Is Typically Seen In Patients Withmentioning
confidence: 99%
“…9 -11 It has been shown that an anti-pan-TGF-␤ monoclonal NAb effectively prevents the expression of extracellular matrix proteins and subsequent myocardial fibrosis in rats with long-term blockade of nitric oxide synthesis. 12 Therefore, using the NAb, we investigated the roles of TGF-␤ in myocardial remodeling in PO rats with a suprarenal abdominal aortic constriction (AC). Also, we examined whether prevention of myocardial remodeling by blocking TGF-␤ function would improve cardiac dysfunction in PO rats.…”
Section: Iastolic Dysfunction Is Typically Seen In Patients Withmentioning
confidence: 99%
“…10 -12 Growth factors, such as transforming growth factor-␤ 1 (TGF-␤ 1 ), have been shown to modulate the expression of adhesion molecules. [13][14][15][16] TGF-␤ 1 , a member of the family of growth factors, is a multifunctional polypeptide. 17 It manifests its biological effects by binding to three distinct TGF-␤ 1 receptors on cell surface (type 1, 2 and 3 [including endoglin]).…”
mentioning
confidence: 99%
“…18 -20 There is evolving evidence that TGF-␤ 1 regulates proliferation and differentiation of cells, remodeling of blood vessels and myocardium after injury, angiogenesis, inflammation, release of cytokines, and lipid metabolism. 10,[15][16][17][18][21][22][23] In keeping with the potential role that TGF-␤ 1 may play in adhesion molecule expression and possibly atherogenesis, Koglin et al 24 showed more extensive atherosclerosis in TGF-␤ 1 -knockout mice. Grainger et al, 25 and later Tashiro et al, 26 showed reduced plasma TGF-␤ 1 levels in patients with atherosclerosis.…”
mentioning
confidence: 99%
“…NO has been recognized to be an important mediator of cellular communication in several preparations such as macrophages, neutrophils, smooth muscle, autonomic nervous system, and central nervous system (Blackman et al, 2000;Koyanagi et al, 2000;Sharma et al, 2000). In this study, exposure of macrophages to IFN-γ and LPS for 48 h was associated with an accumulation of nitrite in the medium, suggesting an enhanced NO production.…”
Section: Discussionmentioning
confidence: 55%